2003
DOI: 10.1002/asi.10367
|View full text |Cite
|
Sign up to set email alerts
|

The effects of domain knowledge on search tactic formulation

Abstract: A search tactic is a set of search moves that are temporally and semantically related. The current study examined the tactics of medical students searching a factual database in microbiology. The students answered problems and searched the database on three occasions over a 9-month period. Their search moves were analyzed in terms of the changes in search terms used from one cycle to the next, using two different analysis methods.Common patterns were found in the students' search tactics; the most common appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
230
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(246 citation statements)
references
References 37 publications
(66 reference statements)
13
230
2
1
Order By: Relevance
“…While several studies on domain knowledge (see Wildemuth, 2004 for a review) have consistently shown that domain experts use different and more search terms (e.g. Marchionini, 1989, Shute & Smith, 1993, Vakkari, 2002, our study suggests that domain experts also have acquired search procedures that enable them to find comprehensive information about a topic.…”
Section: Diagnosis Nodesmentioning
confidence: 58%
“…While several studies on domain knowledge (see Wildemuth, 2004 for a review) have consistently shown that domain experts use different and more search terms (e.g. Marchionini, 1989, Shute & Smith, 1993, Vakkari, 2002, our study suggests that domain experts also have acquired search procedures that enable them to find comprehensive information about a topic.…”
Section: Diagnosis Nodesmentioning
confidence: 58%
“…Domain knowledge or expertise has been shown to affect search behaviors. Users with low domain knowledge are found to have more nonproductive queries (Allen, 1991), use less efficient concepts and make more query reformulation errors (Wildemuth, 2004), and resort to less effective search strategies (Hembrooke, Granka, Gay, & Liddy, 2005). Users with intermediate levels of knowledge about their task fail to select available documents of which they have the most knowledge as compared to users with high or low levels of domain knowledge (Cole, Zhang, Belkin, Liu & Gwizdka, 2011c).…”
Section: Implicit Detection Of Domain Knowledge During Searchmentioning
confidence: 99%
“…Information search in task sessions involves non-linear and conditionalized relationships (Wildemuth, 2004, Qiu, 1993. It is reasonable to suppose such relationships may affect the cognitive effort during the task session.…”
Section: 43mentioning
confidence: 99%
“…However, a number of studies also found little or no correlation between discipline and information seeking behavior (Ellis, Cox, & Hall, 1993;Heinström, 2003;Korobili, Malliari, & Zapounidou, 2011;Sharifabadi, 1996). Some other factors that have been demonstrated to influence information seeking are domain knowledge (Hölscher & Strube, 2000;Jenkins, Corritore, & Wiedenbeck, 2003;Hembrooke, Granka, Gay, & Liddy, 2005;Marchionini, 1997;Wildemuth, 2004;Zhang, Anghelescu, & Yuan, 2005;White, Dumais, & Teevan, 2009), computer and web experience (Aula, 2005;Aula, Jhaveri, & Kaki, 2005;Eshet-Alkalai & Chajut, 2009;Hölscher & Strube, 2000;Hargittai, 2002;Jenkins, Corritore, & Wiedenbeck, 2003;Korobili et al, 2011;Thatcher, 2008;Williamson, Bernath, Wright, & Sullivan, 2008), search experience (Chen, 2009;Hsieh-Yee, 1993;Marchionini, 1997;Tsai, 2009;Williamson et al, 2008) and frequency of use of esources (Griffiths & Brophy, 2005;Haglund & Olsson, 2008;George et al, 2006;Korobili et al, 2006). Some studies have revealed the importance of other people (tutors, instructors, colleagues, librarians, friends, etc.…”
Section: Literature Reviewmentioning
confidence: 99%